Quantum inspired computational intelligence - Bhattacharyya, Siddhartha; Ujjwal Maulik; Paramartha Dutta; TotalBoox; TBX ([Place of publication not identified] : Elsevier Science, 2016)
Quantum Inspired Computational Intelligence: Research and Applications explores the latest quantum computational intelligence approaches, initiatives, and applications in computing, engineering, science, and business. The book explores this emerging field of research that applies principles of quantum mechanics to develop more efficient and robust intelligent systems. Conventional computational intelligence--or soft computing--is conjoined with quantum computing to achieve this objective. The models covered can be applied to any endeavor which handles complex and meaningful information. Brings together quantum computing with computational intelligence to achieve enhanced performance and robust solutions Includes numerous case studies, tools, and technologies to apply the concepts to real world practice Provides the missing link between the research and practice.
Vendor-supplied metadata.
Includes bibliographical references and indexes.
Keywords: Computational intelligence; Quantum computing; COMPUTERS -- General; Computational intelligence; Quantum computing; Computer Science; Information Technology